Evaluation of Six Patients with Pulmonary Carcinosarcoma with a Literature Review - Sinem Nedime Sökücü; Celalettin Kocatürk; Nur Ürer; Yaşar Sönmezoğlu; Levent Dalar; Levent Karasulu; Sedat Altın; Mehmet Ali Bedirhan (The Scientific World Journal)
Background. Carcinosarcoma of the lung is a rare malignant neoplasm. We evaluated the diagnosis and treatment of six carcinosarcoma cases, including a synchronous tumour and a solitary pulmonary tumour, along with the clinical and histological features and survival times. Methods. From a retrospective analysis of 1076 non-small-cell lung cancer resections performed between January 1996 and January 2011, six patients (0.5%) with pulmonary carcinosarcoma (all males; mean age 58 years; range 53–66) who underwent surgical treatment were studied. Results. The mean tumour pathological T diameter was 7.2 cm (median 6 cm, range 3–14.5 cm). Only one patient was diagnosed with carcinosarcoma preoperatively. The clinical presentation and tumour localisations differed. The operations performed were a lobectomy (n=4), pneumonectomy (n=1), and bilobectomy (n=1). Histologically, the epithelial characteristics of the tumours were consistent with squamous cell carcinoma in most of the patients. A complete resection was performed in all six patients. No mortality occurred in the early postoperative period. The median survival time was 9 (3–25) months. Conclusion. The preoperative diagnosis of carcinosarcoma of the lung is difficult due to the composition of the different histopathological structures. Complete surgical resection is the treatment of choice for pulmonary carcinosarcoma, although further studies are needed.